ANALISIS TEGANGAN PADA TEROWONGAN BAWAH TANAH DENGAN METODE ELEMEN HINGGA - Yessy Yessy; Leo S Tedianto (JMTS: Jurnal Mitra Teknik Sipil, 2020)
Construction of tunneling in Indonesia is a new thing to be implemented, especially in the capital city of Jakarta, which has land issues for surface transportation. In the construction stage of tunnels, the problem of deformation and stress to the surface of the excavation needs to be considered carefully. Therefore, the purpose of this paper is to analyze the stresses and deformations that occur in underground tunnels during the construction stage using the finite element method. Modeling is done in full 3 dimensions using a finite element based MIDAS GTS NX program. The results of the study showed that the increase in construction stage, the value of deformation that occurs in development will increase. It also occurs in stress, the more construction phases increase the greater the stress value. Shield release has an effect on increasing the stress, causing the stress to increase even greater. This study uses a hybrid mesher element to model the soil and tunnel layers. From this modeling is expected to be the beginning of complex and good tunnel modeling in the future.Keywords: Tunnel, MIDAS GTS NX, stress, Deformation, construction stage, finite element method.